Kinerja Keuangan dan Harga Saham - Mulyadi, Robi; Rinaldo , Dito (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
Businesses in Indonesia are benefiting from the rapid growth and expansion of the global economy. This is evident by the number of companies registering to sell their shares on the Indonesia Stock Exchange (IDX). Companies listed on the Indonesia Stock Exchange must have a good going concern in order to stay in the capital market. This is because companies listed on the IDX strive to increase the profitability of their business and obtain more funds, and investors will receive dividends and capital gains. Finding out how financial performance affects stock prices in construction businesses listed on the Indonesia Stock Exchange (IDX) for the years 2021–2023 is the aim of this study. Researchers use quantitative methods with descriptive and verification approaches to collect data for research. Data normality, multicolonierity, heterocedacity, autocorrelation, multiple linear regression, determination coefficient, and hypothesis testing are among the data analysis methods employed. Based on the study's findings, it can be said that while ROE influences stock prices, ROA has no effect at all. Stock prices are impacted by ROA and ROE at the same time